Ongoing Drainage Reorganization Driven by Rapid Lake Growths on the Tibetan Plateau. Issue 24 (10th December 2021) - Liu, Kai; Ke, Linghong; Wang, Jida; Jiang, Ling; Richards, Keith S.; Sheng, Yongwei; Zhu, Yunqiang; Fan, Chenyu; Zhan, Pengfei; Luo, Shuangxiao; Cheng, Jian; Chen, Tan; et al.
Abstract: Drainage reorganization generally occurs on geological time scales under unstable river network conditions. A few local‐scale studies indicate that recent climatic changes might accelerate the drainage reorganization process. However, large‐scale drainage reorganization during the modern era is rarely documented. This study examines ongoing drainage reorganization on the endorheic Tibetan Plateau (TP) as a primary result of drastic lake expansion. A total of 11 drainage system reorganization events comprising 24 different lake basins and covering a total area of 61, 115 km 2 occurred between 2000 and 2018. Assuming the continued growth rate of TP lakes, we project another 20 basins will be reorganized before 2030. These drainage basin reorganizations not only alter hydrological processes in the endorheic TP but may also cause the endorheic‐exorheic transition, leading to the upstream sprawl of the Yangtze River Basin and posing outburst flooding risks on China's key infrastructure such as the Qinghai‐Tibet Railway. Plain Language Summary: Recent climatic changes have intensified the global hydrologic cycle, and have likely accelerated drainage system evolution. We have provided a holistic picture of ongoing drainage reorganization driven by drastic lake expansions on the Tibetan Plateau (TP). Our results indicate that 24 different lake drainage systems have undergone reorganization between 2000 and 2018, and the number of basins is expected to increase to 44 by the year 2030. One notable drainage reorganization is between the endorheic Lake Yanhu and the exorheic Chumaer river, resulting in the upstream expansion of the Yangtze River Basin. These findings provide an increased understanding of ongoing drainage reorganization events driven by climatic changes. Further, this work advances our understanding of the connections between ongoing hydrologic changes and their effect on related geological disasters (e.g., outburst floods) within the TP. Key Points: Rapid lake growths drive large‐scale drainage reorganizations on the Tibetan Plateau 24 lake drainage systems have undergone reorganization from 2000 to 2018 and this number is expected to increase to 44 by the year 2030 The northern portion of the upstream Yangtze basin has expanded by around 8, 400 km 2 due to an endorheic‐exorheic transition